Synthesis of Red Fruit Oil (Pandanus Conoideus) Emulsion with Tween 80 Surfactant and Alginate Co-Surfactant - Indriyani, Nita; Ramadhani, Layli Putri; Muzdalifah, Nirmalani; Sari, Amalia Puspita; Fathurrahman, F. (Jurnal Teknik Kimia dan Lingkungan, 2024)
Red fruit (pandanus conoideus) is one of the natural biological resources that contains lipid compounds that are beneficial and important for health. However, the content of red fruit oil components is sensitive to oxygen, light, and heat, so it impacts damage to the content and a relatively short shelf life. The emulsification method can increase the benefits and shelf life of red fruit oil. Emulsions can be stored by preserving active substances in their core and protecting them with a shell layer. Adding alginate to the water phase can increase the stability of the emulsion against aggregation because these molecules can cause steric and electrostatic repulsion between droplet interfaces. This study aims to synthesize red fruit oil emulsions with alginate as a co-surfactant. The variables observed were the ratio of ingredients, the effect of speed, and the time of emulsification stirring. The study's results, namely alginate, can be used as a co-surfactant in the synthesis of red fruit oil emulsions. The ratio of red fruit oil emulsion ingredients is 1% weight/volume, tween 80 1% weight/volume, and alginate 2% weight/volume of a total volume of 40 ml. The emulsification process conditions were carried out at room temperature with a stirring speed of 25,000 rpm and a stirring time of 10 minutes. The resulting emulsion is an oil-in-water emulsion (m/a). The emulsion is dominated by hydrophilic or polar components caused by tween 80 surfactants and alginate co-surfactants. In addition, the creaming formation time occurred after 216 hours, and the separation time occurred after storage for 552 hours.